Pengaruh Kesadaran Merek, Asosiasi Merek, Kualitas Yang Dipersepsikan, Dan Citra Merek Terhadap Keputusan Pembelian Sabun Mandi Cair Di Kota Ambon - Imelda Talahatu (Jurnal Administrasi Terapan, 2024)
This study aims to analyze the influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Image on the Purchase Decision of Liquid Soap in Ambon City. The research uses a quantitative approach with a survey method. The design of this study is both descriptive and causal, aiming to describe the relationships between the research variables and determine their impact on purchase decisions. The population in this study consists of all consumers in Ambon City who have purchased and used liquid soap products. This research employs a purposive sampling technique, where the sample is selected based on specific criteria, namely consumers who have purchased liquid soap within the last three months. The sample size taken is 100 respondents. Multiple Linear Regression Analysis is used to analyze the influence of brand awareness, brand association, perceived quality, and brand image on purchase decisions. The results of this study indicate that brand awareness, brand association, perceived quality, and brand image all have a significant impact on the purchase decision of liquid soap in Ambon City. Keywords: Brand Awareness, Brand Association, Perceived Quality, Buying Decision